Automation and Adaptation: Reshaping journalistic labor in the newsroom library. (February 2020) - Boyles, Jan Lauren; Meisinger, Jared
In the digital transition within American newspapers, newsroom librarians were among the first newsworkers to have their labor automated. In response, these practitioners operating in converged newsrooms shifted their on-the-job routines and roles to align with the increasing centrality of machines in journalistic production. Using an actor-network approach, this research integrates in-depth interviews to explore how American newsroom librarians interface with machines in acting as guardians of institutional knowledge within news organizations. Examining the modern duties of newsroom librarians can provide broader context for the next generation of industry automation in journalistic practice.